An evaluation of histopathological findings of skin biopsies in various skin disorders - Narang, Sanjeev; Jain, Ravi (Annals of Pathology and Laboratory Medicine, 2015)
Background - Skin conditions are among the most common health problems in India. Skin biopsy is most common diagnostic technique for diagnosing skin disease. The interpretation of a skin biopsy requires clinicopathological correlation. Methods: The present study was undertaken in the Department of Pathology, M.G.M Medical College and M.Y. Hospital, Indore (M.P) to determine the incidence and age-sex distribution of various skin diseases, to study the various histopathological changes encountered in the course of the study and to establish clinic pathological correlation. A total number of 262 biopsies retrieved from the archives during the period of January 2007 to June 2008 along with skin biopsies sent for histopathological evaluation during June 2008 – June 2010 were included in the study. On the basis of histopathological classification the skin disorders are divided into eight groups. Result: Maximum number of cases belonged to group V disorders i.e. disorders showing perivascular, diffuse and granulomatous infiltrates of the reticular dermis 65(24.8 %), followed by group VI disorders that is tumors and cysts of the dermis 28(10.7 %). Out of 262 skin biopsies which came for Histopathological evaluation, 137 (52.3 %) cases were given definite diagnosis by microscopic examination of slides. Amongst 216 cases, clinico-histopathological correlation was seen in 95(44 %) cases. Highest number of cases 68(25.95 %) were observed in the age group of 21-30 years, with majority of the cases were male 149(56.9 %) while 113(43.1 %) cases were female. Conclusion: Leprosy is still most prevalent, thereby emphasizing stronger measures to control it.